The fortress of the treasure queen - Abbott, Tony.; Merrell, David (New York : Scholastic, 2004)
Eric and friends are forced to ask their worst enemy, Lord Sparr, for help when Ko regains power and tries to destroy Jaffa City with a lightning-powered submarine discovered in a secret fortress.
"A Little Apple paperback."
5.2
3-6
3-6
650
Keywords: Droon (Imaginary place) -- Fiction; Genies -- Fiction; Magic -- Fiction; Fantasy; Droon (Imaginary place) -- Fiction; Genies -- Fiction; Magic -- Fiction; Fantasy fiction